IMPLEMENTASI TAKWIL DALAM TAFSIR AL-KASYSYAF OLEH AL-ZAMAKHSYARIY - Bilfahmi Putra (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This problem is motivated by the very striking difference between al-Zamakhsyariy with other mufassir in interpreting (mentakwil) verses of the Qur'an. The subject matter is: how can the implementation of takwil that conducted by al-Zamakhsyariy in the Tafsir al-Kasysyaf, limited by one restrictions; how the results of the form takwil. This study aims: to found the form of takwil that clear. This research is library research, primary data source is al-Kasysyaf, and secondary data source is books, journals scientific and documents related with these discussion, the methods used in this study is qualitative method and content analysis. While the results of penakwilan process conducted al-Zamakhsyariy is; Al-Zamakhsyariy mentawkilkan the verses mutasyabih, and the verses or pronunciations that are contrary to the understanding of the Mu'tazilah, mentawkilkan the verses not mutasyabih.